1997
DOI: 10.1007/bf02773800
|View full text |Cite
|
Sign up to set email alerts
|

A uniformly convex hereditarily indecomposable banach space

Abstract: We construct a uniformly convex hereditarily indecomposable Banach space, using similar methods as Gowers and Maurey in [GM] and the theory of complex interpolation for a family of Banach spaces of Coifman, Cwikel, Rochberg, Sagher and Weiss ( [5a]). n i=1 x i , then we say that X satisfies a lower f -estimate.Let q > 1 in R, q ′ such that 1/q + 1/q ′ = 1. Let θ ∈ ]0, 1[ , and p be the number defined by 1/p = 1 − θ + θ/q.Let S be the strip {z ∈ C/Re(z) ∈ [0, 1]}, δS its boundary, S 0 the line {z/Re(z) = 0}, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 6 publications
0
59
0
2
Order By: Relevance
“…space) if it does not contain any decomposable subspace. The class of hereditarily indecomposable Banach spaces was first introduced and investigated by Gowers and Maurey in [7] (see also [4]). One of the main facts relating to this class is the following result due to Gowers and Maurey [7].…”
Section: Hereditarily Indecomposable Banach Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…space) if it does not contain any decomposable subspace. The class of hereditarily indecomposable Banach spaces was first introduced and investigated by Gowers and Maurey in [7] (see also [4]). One of the main facts relating to this class is the following result due to Gowers and Maurey [7].…”
Section: Hereditarily Indecomposable Banach Spacesmentioning
confidence: 99%
“…[7,4]), strongly continuous semigroups exhibit a nice behavior. In particular, we establish that the infinitesimal generator of any strongly continuous group is necessarily bounded (which seems to be a feature of this class of spaces).…”
mentioning
confidence: 99%
“…Now, on one hand, Gowers and other analysts are using the "arbitrarily distortable" technique of HI spaces developed by Gowers, Maurey and other mathematicians to other mathematical topics (see, for example, [28,29,30,[31][32][33][34][35][36], [37] and [38]). On the other hand, many mathematicians have been investigating properties of HI spaces (see, [39,40,[41][42][43]), [44,45,46,47] and [48][49][50]). It has been already found that a space of HI type or the Gowers-Maurey type can be so "bad" that it has no subspace of infinite dimensions with a separable dual [14], and can be so "nice" that it has an equivalent uniformly convex norm [42].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many mathematicians have been investigating properties of HI spaces (see, [39,40,[41][42][43]), [44,45,46,47] and [48][49][50]). It has been already found that a space of HI type or the Gowers-Maurey type can be so "bad" that it has no subspace of infinite dimensions with a separable dual [14], and can be so "nice" that it has an equivalent uniformly convex norm [42]. Yet a lot of long-standing open problems would be resolved by constructing various types of hereditarily indecomposable Banach spaces, especially, non-separable HI (see, for instance, [27,51]).…”
Section: Introductionmentioning
confidence: 99%
“…If the answer is positive then Theorem 2.2 will imply that every quasi-nilpotent operator on a super-reflexive Banach space has a non-trivial invariant subspace. Then, every strictly singular operator on a super-reflexive Hereditarily Indecomposable complex Banach space has a non-trivial invariant subspace (see [7]), and hence the space constructed in [6] would provide a positive solution to the I.S.P..…”
Section: Introductionmentioning
confidence: 99%